Status And Perspectives of Digitalization on Public Accounting - Elena Alina OLARU (COLBEA); Elena HLACIUC; Anisoara APETREI; Mihaela TULVISCHI; Anatol GRAUR (Communications of International Proceedings, 2022)
Digitalization, through the technological resources dedicated to communication and information transfer, shapes the daily work and operational processes of all modern organizations, sometimes completely transforming organizations and processes. Widespread use of digital technology will benefit from increased transparency and efficiency in all sectors of the economy, significantly transforming the way public institutions operate and providing value to stakeholders. This study investigates the current impact of digitalization on the accounting system in public institutions and future development trends, responsibilities for implementation, but also the obstacles already encountered.
Keywords: accounting; public institutions; IPSAS; digitization.